The Legal and Diplomatic Implications of France’s Security Disengagement from the Sahel: A Case Studies of Niger, Mali, and Burkina-Faso, 2021–2024 - Fasinu, Emmanuel Selome; Aseseke, Stephen Adewale; Eloche, John Adakole (Journal of Contemporary International Relations and Diplomacy, 2025)
This study critically explored the shifting landscape of diplomacy, security cooperation, and foreign policy realignment in Niger, Mali, and Burkina-Faso following France’s military withdrawal from the Sahel region. The study is justified by the need to examine emerging geopolitical realignments amid growing anti-French sentiments and increasing regional security challenges. The core problem addressed lies in understanding the implications of France’s exit on regional stability and the rise of new partnerships, particularly with Russia and regional bodies like ECOWAS. The research was guided by four objectives and corresponding questions, focusing on public perception of France’s withdrawal, the regional security outlook, the realignment of foreign alliances, and the impact on diplomatic relations. Grounded in dependency theory, the study explained how colonial and neo-colonial dynamics have influenced present-day diplomatic orientations and the shift toward sovereign-led partnerships. The scope covered selected urban populations across the three countries. Using a mixed-methods approach, both quantitative and qualitative data were collected from a total sample of 750 participants, with 250 respondents from each country. Data analysis revealed growing public discontent with France’s presence, increased support for Russian involvement, and a desire for regionally-driven security solutions. Despite fears of a security vacuum, the study found a strong preference for post-colonial autonomy and diplomatic diversification. Recommendations include strengthening regional security mechanisms, promoting sovereign foreign policy decisions, investing in local capacity, and critically monitoring new alliances. In conclusion, the study highlighted the transformative potential of the Sahel’s diplomatic trajectory, stressing the need for localized solutions and sustainable international relations beyond traditional colonial legacies.